Brewing Happiness Design Aspects of Coffee Representation in Cozy Games - Krzysztof Chmielewski; Jakub Majewski (Replay)
This paper examines the way coffee is represented and used in cozy games. As a genre, cozy games are defined by the concepts of safety, abundance, and softness, which together establish a sense of coziness. Coffee, commonly associated with casual and friendly social situations, has a potential to be a strong contributor to coziness within cozy games. To explore this, the authors identified 27 cozy games containing coffee-related elements, and then performed a qualitative analysis on their content. The analysis found it was comparatively rare for coffee themes to strongly impact the overall game experience; however, there was a significant tendency for coffee to amplify the game’s overall sense of coziness.